Jetty Extension Study Due to Addition of Power Capacity on Thermal Water Dispersion at PLTGU Grati Pasuruan - Cahya, Ilham; Suntoyo, Suntoyo; Lailiyah, Inayatul; Nurdin, Jihannuma Adibiah (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
PLTGU (Gas and Steam Power Plant) is a combination of gas power plant and steam power plant. PLTGU requires a cooling water systems during its operational life. The required amount of cooling water will increased along to increased power capacity of power plant. This project contains jetty extension study due to the addition of power capacity on thermal water dispersion at PLTGU Grati, Pasuruan. The results show using Delft3D hydrodynamic model, The alternative model showing quite good performance decreased temperature of cooling water on average 0.7975 oC at inlet canal. But it only need 2.5 oC increase of seawater temperature to decrease 0.33% efficiency, so it might change nothing to thermal power plant efficiency compared to the model result. Considering to the increasing risk of sedimentation rate, this alternative might be poor layout but further research needed. Still the best choice is on existing jetty design.